Dissecting the Potential Roles of Nigella sativa and Its Constituent Thymoquinone on the Prevention and on the Progression of Alzheimer's Disease - Cascella, Marco; Bimonte, Sabrina; Barbieri, Antonio; Del Vecchio, Vitale; Muzio, Maria Rosaria; Vitale, Andrea; Benincasa, Giulio; Ferriello, Anna Bella; Azzariti, Amalia; Arra, Claudio; Cuomo, Arturo (Frontiers in Aging Neuroscience, 2018)
Several nutraceuticals have been investigated for preventing or retarding the progression of different neurodegenerative diseases, including Alzheimer’s disease (AD). Because Nigella sativa (NS) and its isolated compound thymoquinone (TQ) have significant anti-oxidant and anti-inflammatory proprieties, they could represent effective neuroprotective agents. The aim of this review is to analyze and to summarize the results of in vitro and in vivo studies on the potential effects of NS/TQ in the prevention and in the treatment of AD. The quality of evidence for each included animal study has been assessed by using a modified CAMARADES (Collaborative Approach to Meta-Analysis and Review of Animal Data from Experimental Studies) 10-item checklist. MEDLINE, EMBASE databases were searched for relevant articles published up to July 2017. Additionally, a manual search was performed. The database search yielded 38 studies, of which 18 were included in this manuscript. Results from these approaches suggest that NS or TQ could represent an effective strategy against AD due to the balancing of oxidative processes and the binding to specific intracellular targets. The overall effects mainly regard the prevention of hippocampal pyramidal cell loss and the increased cognitive functions.